The Role of Competency-Based Nursing Education in Improving the Quality of Health Services - S. Darmojo, Hardjito; Al-Bahra, Al-bahra; Suciana, Ewin (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2024)
Competency-based nursing education is a strategic approach that emphasizes the mastery of measurable knowledge, skills, and professional attitudes to ensure graduates are capable of providing quality healthcare services. This article aims to analyze the role of competency-based nursing education in improving the quality of healthcare services. The method used is a systematic literature review of journals, institutional reports, and current nursing education policies, as well as a case study of the application of clinical competencies in primary healthcare facilities. The study results indicate that integrating a competency-based curriculum improves nurses' clinical skills, strengthens decision-making, and minimizes errors in care. Competently trained graduates are able to respond effectively to patient needs, improve patient safety, and support the implementation of national and international healthcare standards. Furthermore, competency-based education fosters a culture of continuous professional development, strengthens interprofessional teamwork, and increases patient satisfaction. These findings confirm that strengthening competency-based nursing education not only focuses on academic achievement but also has a direct impact on the quality of healthcare services, making them safer, more effective, and more sustainable. Recommendations from this article emphasize the need for regular curriculum evaluation, strengthening standardized clinical practices, and collaboration across educational institutions and healthcare facilities to ensure the relevance of competencies to the needs of the healthcare system.